(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Andoy’s Clothing Store is a small wholesale shop in Bagumbong, Caloocan City, that offers a variety of ready-made clothes. The store has two employees who manage it and aim to provide generational fashion trends while catering to customer preferences. Their products include casual wear, jeans, swimwear, blouses, shirts, shorts, bras, and sleepwear. However, based on observations, the store needs promotional tools or marketing strategies to attract customers and improve satisfaction. To collect additional information, we utilized quantitative research. A total of 100 customers were surveyed using a purposive sampling technique. Online survey questionnaires were distributed to gather information, and statistical tools such as frequency and percentage, weighted mean, and ranking were used for analysis. The survey questionnaire was aimed to determine customer demographics and their responses to sales promotion, direct marketing, and personal selling. One hundred customers received validated questionnaires, revealing no significant difference in promotional tool use based on age, gender, or purchase frequency. However, there was a significant difference in using income-based promotional tools.